Evaluation of Supervision of the 21st Century Learning Program of the Prima Swarga Bara Education Foundation - Imanuddin, Hamzah Nur; Mulawarman, Widyatmike Gede; Azainil, Azainil (EduLine: Journal of Education and Learning Innovation, 2025)
YPPSB is an educational institution that implements 21st century learning by providing technological devices in the form of smart TVs in every classroom, even installing CCTV in junior high school classrooms. Programmed supervision at YPPSB is an effort to manage learning in accordance with educational developments. This phenomenon is the background for research that aims to evaluate the context, input, process, and product of YPPSB's 21st century learning supervision program. This study uses a qualitative approach that describes the learning supervision program with the CIPP model evaluation method (Context, Input, Process, and Product) based on data collection techniques in the form of in-depth interviews, data observation, and analysis of relevant documents. Data analysis techniques are carried out with interactive models including data collection, data reduction, data display, and conclusion drawing. Data validity checks are carried out with credibility tests including extended observations, increased persistence, triangulation, discussions with colleagues, negative case analysis, and member checks. The results of the context evaluation study explain that the YPPSB Principal conveyed the background, needs, and objectives of supervision verbally to the Teacher in the second week before implementation; the results of the input evaluation explain that YPPSB has supervisor qualifications in accordance with Permendikbudristek No. 40 of 2021 but does not require a code of ethics; the results of the process evaluation explain that YPPSB uses supervision instruments based on the 2007 process standards, carries out a direct contact approach (TK and SD) and collaborative (SMP), with individual techniques; and the results of the product evaluation explain that YPPSB presents reports by collecting supervision instrument documents, not presenting them according to the direction of the Ministry of Education and Culture (2019).